2014
DOI: 10.1007/s12282-014-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Breast Cancer Society clinical practice guideline for epidemiology and prevention of breast cancer

Abstract: Descriptive epidemiology of breast cancer in Japan MortalityThe vital statistics of the Ministry of Health, Labour and Welfare show that the crude and age-adjusted death rates of patients with breast cancer increased consistently from the 1960s to 2011, but decreased in 2012. The number of deaths due to breast cancer in women was 12,529 in 2012. The crude death rate was 19.4 per 0.1 million population and ranked fifth highest, behind colon/rectum, lung, stomach, and pancreatic cancers in descending order. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…A history of never breastfeeding, and a positive history of benign breast disease were identified as environmental risk factors for premenopausal women, while a history of never breastfeeding, higher BMI, and the presence of hyperlipidemia were environmental risk factors for postmenopausal women in our analysis. These environmental factors are established risk factors for breast cancer [ 8 ]. A history of breastfeeding and BMI were included as risk factors in the Gail model, which is one of the breast cancer risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A history of never breastfeeding, and a positive history of benign breast disease were identified as environmental risk factors for premenopausal women, while a history of never breastfeeding, higher BMI, and the presence of hyperlipidemia were environmental risk factors for postmenopausal women in our analysis. These environmental factors are established risk factors for breast cancer [ 8 ]. A history of breastfeeding and BMI were included as risk factors in the Gail model, which is one of the breast cancer risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of risk factors may vary by breast cancer subtype, especially those defined by ER status, and ethnicity [ 6 , 7 ]. The reported risk factors can be divided into three categories; environmental factors, endogenous factors including hormones, and common genetic variants including single nucleotide polymorphisms (SNPs) [ 8 ]. Previous studies demonstrated that inclusion of common genetic variants as well as environmental factors could improve risk assessment models [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of breast MRI screening for women bearing BRCA1 or BRCA2 gene mutations has been newly adopted as a clinical question (CQ) in the Japanese Breast Cancer Society Clinical Practice Guideline. 12 …”
Section: Discussionmentioning
confidence: 99%
“…After revision every 3 years, these guidelines were published in 2011 as the JBCS Clinical Practice Guidelines for Epidemiology and Prevention of Breast Cancer. Revised editions were published in 2013 [ 5 ] and 2015 [ 6 ], with revisions made every 2 years to keep up with the rapid accumulation of data and changes in the standard of care. A fully revised edition was published in 2018.…”
Section: Introductionmentioning
confidence: 99%